BEST PRACTICES FOR HIPAA-COMPLIANT EDI IMPLEMENTATIONS: A COMPREHENSIVE GUIDE - Pramod Kumar Muthyala (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article examines the evolution and implementation of Electronic Data Interchange (EDI) in healthcare settings, focusing on HIPAA compliance, security measures, and operational efficiency. The article explores various aspects of EDI implementation, including transaction standards, error-handling procedures, and compliance monitoring systems. It investigates the transformation of healthcare information exchange through EDI adoption, analyzing the impact on cost reduction, processing efficiency, and security enhancement. The article includes detailed case studies of successful implementations, best practices for security protocols, and strategies for optimizing revenue through EDI integration. The article demonstrates how modern healthcare organizations can leverage EDI systems to improve operational workflows, ensure regulatory compliance, and enhance patient care delivery while maintaining robust security measures.